The Development of Instagram Filter-Based Learning Media for Mathematics in Junior High School - Valeria Yekti Kwasaning Gusti; Uliya Khoirun Nisa; Rika Aprianti; Khoirotun Nadiyyah; Egi Ryan Aldino (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The rise of the digital age and STEM-based occupations (Science, Technology, Engineering, and Mathematics) has increased the significance of mathematics skills in the workplace and in the classroom. At the same time, the usage of social media such as Instagram, as well as Instagram's effects and filters, has become widespread among adolescents, particularly students. The purpose of this study is to develop an Instagram filter-based learning media for junior high school students. The material used in the development of the Instagram filter is the material on Relations and Functions that is difficult to understand by students based on a student needs questionnaire. This study developed an Instagram-based learning media by administering validation and feasibility tests to material experts, media experts, and student response questionnaires in the form of a small-scale trial. The designed Instagram filter-based learning media received an average score of 83.22 percent with a very good interpretation based on the validation and feasibility tests.